PERFORMING ART AS AN ETHNOCULTURAL MODUS OF REPRESENTATION OF THE NATIONAL IDEA IN THE CONDITIONS OF CIVILIZATIONAL CHANGES: CULTURALOGICAL- ART STUDIES - Шумакова, Світлана; Островська, Марина; Лебедь, Андрій; Сікалов, Ігор (SWorldJournal, 2025)
The article reflects a culturalogical and art studies of representations of national and cultural identity in the modern cultural space with an emphasis on the integrative, determining and identifying role of performing arts, capable of consolidating ethn